The Accumulated Response of Deciduous Liquidambar formosana Hance and Evergreen Cyclobalanopsis glauca Thunb. Seedlings to Simulated Nitrogen Additions - Zhang, Zhenzhen; Zhao, Yamin; Zhang, Xiaoyan; Tao, Sichen; Fang, Xiong; Lin, Xingwen; Chi, Yonggang; Zhou, Lei; Wu, Chaofan (Frontiers in Plant Science, 2019)
Nitrogen depositions in the Yangtze River Delta have is thought to shift the coexistence of mixed evergreen and deciduous species. In this study, the seedlings of the dominant evergreen species Cyclobalanopsis glauca Thunb. and the deciduous species Liquidambar formosana Hance from the Yangtze River Delta were chosen to test their responses to simulated N additions using an ecophysiological approach. N was added to the tree canopy at rates of 0 (CK), 25 kg N ha−1 year−1 (N25) and 50 kg N ha−1 year−1 (N50). The leaf N content per mass (Nm, by 44.03% and 49.46%) and total leaf chlorophyll content (Chl, by 72.15% and 63.63%) were enhanced for both species, and C. glauca but not L. formosana tended to allocate more N to Chl per leaf area (with a higher slope). The enhanced N availability and Chl promoted the apparent quantum yield (AQY) significantly by 15.38% and 43.90% for L. formosana and C. glauca, respectively. Hydraulically, the increase in sapwood density (ρ) for L. formosana was almost double that of C. glauca. Synchronous improved sapwood specific hydraulic conductivity (KS, by 37.5%) decrease for C. glauca induced a significant reduction in stomatal conductance (gs) (p < 0.05) in the N50 treatments, which is in contrast to the weak varied gs accompanied by a 59.49% increase in KS for L. formosana. As a result, the elevated maximum photosynthesis (Amax) of 12.19% for L. formosana in combination with the increase in the total leaf area (indicated by a 37.82% increase in the LAR-leaf area divided by total aboveground biomass) ultimately yielded a 34.34% enhancement of total biomass. In contrast, the Amax and total biomass were weakly promoted for C. glauca. The reason for these distinct responses may be attributed to the lower water potential at 50% of conductivity lost (P50) for C. glauca, which enables higher hydraulic safety at the cost of a weak increase in Amax due to the stomatal limitation in response to elevated N availability. Altogether, our results indicate that the deciduous L. formosana would be more susceptible to elevated N availability even if both species received similar N allocation.